Contenido de verbascósido en poblaciones de “Poleo” (LIPPIA TURBINATA GRISEB.) de la Región Central de la Argentina - Guariniello, Julian; Risso, Oscar Ariel; Galli, Maria Carolina; Moscatelli, Valeria A.; Di Leo Lira, Paola Maria del Rosario; Marchetto, L.; Dobrecky, Cecilia; Flor, Sabrina; van Baren, Catalina María; Retta, Daiana S. (Sociedad Argentina de Botánica, 2023)
Poster